2016
DOI: 10.1007/s40139-016-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles as Vehicles for Tissue Regeneration: Changing of the Guards

Abstract: Purpose of ReviewMicrovesicles (MVs) have been recognised as mediators of stem cell function, enabling and guiding their regenerative effects.Recent FindingsMVs constitute one unique size class of extracellular vesicles (EVs) directly shed from the cell plasma membrane. They facilitate cell-to-cell communication via intercellular transfer of proteins, mRNA and microRNA (miRNA). MVs derived from stem cells, or stem cell regulatory cell types, have proven roles in tissue regeneration and repair processes. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Chain Reaction. Prior to quantitative real-time polymerase chain reaction (qRT-PCR), total RNAs were extracted and reverse-transcribed using random hexamers, as previously described [10]. RT-PCR was performed using 10 ng of cDNA/tube and SYBR Green Mix (Bio-Rad Laboratories, Hercules, CA).…”
Section: Quantitative Real-time Reverse Transcription Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…Chain Reaction. Prior to quantitative real-time polymerase chain reaction (qRT-PCR), total RNAs were extracted and reverse-transcribed using random hexamers, as previously described [10]. RT-PCR was performed using 10 ng of cDNA/tube and SYBR Green Mix (Bio-Rad Laboratories, Hercules, CA).…”
Section: Quantitative Real-time Reverse Transcription Polymerasementioning
confidence: 99%
“…Recently, stem cell-derived substrates and secretomes have been used as therapeutic tools and for cartilage regeneration [1]. Several studies have shown that the therapeutic efficacy of stem cell transplantation is attributable to multiple secreted factors that regulate the surrounding microenvironment to evoke regeneration via a paracrine mechanism [9][10][11]. MSCs secrete an array of growth factors, cytokines, and extracellular vesicles; these enhance collagen type II expression and downregulate matrix metalloproteinase expression in osteoarthritic chondrocytes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cell-derived microvesicles (MV) are a relatively new object of research that represents vesicular fragments of a plasma membrane 100 (150)-1000 nm in diameter, while exosomes are less than 100 (150) nm in size [20,21,69,70]. It was demonstrated that MV are produced by cells both in an unstimulated state and as a result of activation; both at physiological processes and at pathologies [43,44,48,54,57,64,69]. It has been established that MV contain both membrane molecules expressed by a source cell and cytoplasmic molecules: lipids, class I and II MHC molecules, chemokines, cytokines, growth factors, transcription factors, microRNA [8,14,21,63], and messenger RNA [1,68,75].…”
mentioning
confidence: 99%
“…PCs are autologous or allogeneic platelet derivatives with a platelet concentration higher than baseline. PCs can release various bioactive components such as growth factors, cytokines, and platelet‐derived microparticles, which are widely used in different areas of regenerative medicine because of their powerful tissue regeneration and repair capabilities . Accordingly, platelet concentrates exert their action by the active substances released by α‐particles, dense particles, and lysosomes in the platelets.…”
Section: Discussionmentioning
confidence: 99%